The SUPPORT-S Protocol Study: A Postvention Program for Professionals After Patient or User Suicide - Leaune, Edouard; Cuvillier, Bruno; Vieux, Maxime; Pacaut-Troncin, Michèle; Chalancon, Benoît; Perez, Anne-Fleur; Haesebaert, Julie; Chauliac, Nicolas; Poulet, Emmanuel; Durif-Bruckert, Christine (Frontiers in Psychology, 2020)
Exposure to patient or user suicide (PUS) is identified as a challenging occupational hazard for mental health and social work professionals. Professionals exposed to PUS may encounter several ranges of emotional, traumatic or professional impacts in the aftermath. A high proportion of exposed professionals reports a lack of support in the aftermath of PUS. SUPPORT is a postvention program designed to provide a comprehensive, adaptative and effective support to professionals impacted by PUS. The aims of the SUPPORT-S study are to 1) improve the design of the SUPPORT program, 2) evaluate the effectiveness of the program to buffer the emotional, traumatic and professional impacts and to improve the perceived social support for professionals exposed to PUS and 3) provide more insights into the consequences of PUS on both professionals and organizations. Method The SUPPORT-S study is a mixed method collaborative and participatory action research. The simultaneous and complementary collection and analysis of qualitative and quantitative data will offer an in-depth evaluation of the implementation and the effectiveness of the program. The qualitative evaluation includes: a) an ethnographic observation; b) 25 semi-directed interviews with randomized participants; c) an activity analysis with providers of the program; and d) collaborative sharing of the results with providers and participants. The quantitative evaluation includes pre- and post-measures in participants of : a) emotional impact (Differential Emotions Scale IV); b) traumatic impact (Impact of Event Scale-Revised); c) professional impact (non-validated questionnaire) and d) perceived social support (Perceived Social Support Scale for Professionals). The action research design will rely on: a) the cycling process of implementation/evaluation/data sharing/adjustment and b) the participatory approach through data sharing with providers and participants. Triangulation, saturation, randomization and participatory design will also reduce the risk of biases and will improve the generalizability of conclusions. Expected results We expect the SUPPORT-S study to evaluate and improve the design of the SUPPORT program to effectively help professionals to cope with PUS. Conclusion The results of the study will allow us to disseminate an effective and adaptive postvention program for professionals and institutions encountering PUS.